UNVEILING THE HISTORY AND ISLAMIC LAWS THROUGH THE TOMBSTONE OF SIRAJUDDIN ISA IN TUBAN, MAJAPAHIT - Arifia, Sariat; Mahdi, Mizuar; Muhammad, Taqiyuddin; Yaqin, Nurul; Alwi, M. Ali (Ridwan Institute, 2025)
This study explores the historical and religious significance of two Islamic tombstones from the Majapahit era in King King, Tuban, Java. The focus is on Sirajuddin Isa ibn Salahuddin Al Ma'bary's tombstone and an unnamed tombstone in the Mbah Randu complex. Through epigraphic and ornamental analysis, the research reconstructs the history of Islamic propagation in Java between the 13th and 15th centuries. Sirajuddin Isa is identified as a key figure in spreading Islam during the Majapahit period. His tombstone's inscriptions